THE INFLUENCE OF NUTRITION EDUCATIONAL VIDEOS IN PHYSICAL EDUCATION LEARNING ON THE IMPROVEMENT OF HEALTHY FOOD KNOWLEDGE AND ITS IMPACT ON ATTITUDES TOWARD CHOOSING HEALTHY FOODS - Iswahyudi, Iswahyudi (Universitas Muhammadiyah Kuningan, 2025)
Learning is a key process for success; therefore, its implementation must be constructed comprehensively, including the media used in its execution. The need for healthy food, as a primary necessity, must be instilled in students. This process can utilize instructional videos as a medium to provide students with knowledge about healthy food, which may influence their attitudes in choosing healthy food. This study employs a quantitative approach, using a questionnaire as its instrument, consisting of 30 questions distributed to 120 students at SMP Muhammadiyah 6 Wuluhan, Jember. Data analysis was conducted using the PLS model with path analysis. The results show that instructional videos have a significant effect, with a p-value of 0.022 < 0.05. However, the knowledge variable, as an intervening variable, does not have a significant effect on the attitude variable, with a p-value of 0.275 > 0.05. Similarly, the instructional video variable does not have a significant direct effect on the attitude variable, with a p-value of 0.984 > 0.05.